Parameters of photosynthetic energy partitioning - Lazár, Dušan (Journal of plant physiology, 2015)
Almost every laboratory dealing with plant physiology, photosynthesis research, remote sensing, and plant phenotyping possesses a fluorometer to measure a kind of chlorophyll (Chl) fluorescence induction (FLI). When the slow Chl FLI is measured with addition of saturating pulses and far-red illumination, the so-called quenching analysis followed by the so-called relaxation analysis in darkness can be realized. These measurements then serve for evaluation of the so-called energy partitioning, that is, calculation of quantum yields of photochemical and of different types of non-photochemical processes. Several theories have been suggested for photosynthetic energy partitioning. The current work aims to summarize all the existing theories, namely their equations for the quantum yields, their meaning and their assumptions. In the framework of these theories it is also found here that the well-known NPQ parameter ( [Formula: see text] ; Bilger and Björkman, 1990) equals the ratio of the quantum yield of regulatory light-induced non-photochemical quenching to the quantum yield of constitutive non-regulatory non-photochemical quenching (ΦNPQ/Φf,D). A similar relationship is also found here for the PQ parameter (ΦP/Φf,D).
Keywords: Photosynthesis; Light; Chlorophyll; Plant Leaves; Photosystem II Protein Complex; fotosystém II (proteinový komplex); Quantum yield; Energy Metabolism; fluorescence; Chlorophyll fluorescence; energetický metabolismus; chlorofyl; fotosyntéza; Non-photochemical; Photochemical; světlo; listy rostlin; Fluorescence